The songs of Stones River a Civil War novel - Gunderson, Jessica; J Foti, Anthony (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2015)
In late 1862 young James of Murfreesboro is a proud Southerner who takes on the responsibility of providing for his newly widowed mother and younger sister by working for his neighbor alongside the field slave Eli--an experience that calls into question many of his cherished beliefs about slavery and the War
A gift from book Africa
English stories
1 2 13 15
Keywords: African Americans -- Tennessee -- Juvenile fiction; Slaves -- Tennessee -- Juvenile fiction; Teenage boys -- Tennessee -- Juvenile fiction